Pengaruh Media Puzzle pada Materi Pecahan di SD PAB Lubuk Pakam Tahun Ajaran 2022/2023 - Pranata, Reza; Hariati, Emy; Ramadhan, Nuri (Multiverse: Open Multidisciplinary Journal, 2024)
This research aims to find out how big the influence on Learning Achievement. This research is a type of qualitative research. In this case, qualitative research is descriptive, ie the data collected is more in the form of words or pictures than numbers which aims to determine or describe the development of learning methods such as the PBL method on student achievement. The method used to analyze the data is library research, which is a type of qualitative research. The research instrument is a person or human instrument, namely the researcher himself. To be able to become an instrument, the researcher must have the provision of theory and broad insight, so as to be able to ask questions, analyze, take pictures, and construct the social situation under study to be clearer and more meaningful. The data analysis technique used is data reduction; data presentation; and drawing conclusions/verification. The results showed that the Problem Based Learning Model can be used to improve achievement in learning mathematics, and the Problem Based Learning Method can make students have achievement in learning mathematics because it is directly related to the real world, so students feel mathematics is very useful and achievement it will increase.